The Role of Atrial Fibrosis Detected by Delayed - Enhancement MRI in Atrial Fibrillation Ablation - Kis, Zsuzsanna; Hendriks, Astrid A.; Muka, Taulant; Bramer, Wichor M.; Kovacs, Istvan; Szili-Torok, Tamas (Current Medical Imaging, 2020)
Introduction: Atrial Fibrillation (AF) is associated with remodeling of the atrial tissue, which leads to fibrosis that can contribute to the initiation and maintenance of AF. Delayed- Enhanced Cardiac Magnetic Resonance (DE-CMR) imaging for atrial wall fibrosis detection was used in several studies to guide AF ablation. The aim of present study was to systematically review the literature on the role of atrial fibrosis detected by DE-CMR imaging on AF ablation outcome. Methods: Eight bibliographic electronic databases were searched to identify all published relevant studies until 21st of March, 2016. Search of the scientific literature was performed for studies describing DE-CMR imaging on atrial fibrosis in AF patients underwent Pulmonary Vein Isolation (PVI). Results: Of the 763 citations reviewed for eligibility, 5 articles (enrolling a total of 1040 patients) were included into the final analysis. The overall recurrence of AF ranged from 24.4 - 40.9% with median follow-up of 324 to 540 days after PVI. With less than 5-10% fibrosis in the atrial wall there was a maximum of 10% recurrence of AF after ablation. With more than 35% fibrosis in the atrial wall there was 86% recurrence of AF after ablation. Conclusion: Our analysis suggests that more extensive left atrial wall fibrosis prior ablation predicts the higher arrhythmia recurrence rate after PVI. The DE-CMR imaging modality seems to be a useful method for identifying the ideal candidate for catheter ablation. Our findings encourage wider usage of DE-CMR in distinct AF patients in a pre-ablation setting.
Keywords: atrial fibrosis